2019
DOI: 10.1021/acsomega.9b01437
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Tautomeric Forms and Neutral-Cationic Forms in the Cocrystals of Sulfamethazine with Carboxylic Acids

Abstract: The cocrystals of sulfamethazine with different acids, namely, 2-mercaptophenylcarboxylic acid, 2,6-pyridinedicarboxylic acid, 4-(4-hydroxyphenylazo)phenylcarboxylic acid, 3-(4-hydroxyphenyl)propanoic acid, and 4-(phenyl)phenylcarboxylic acid, are studied here. Each has distinct notable supramolecular features. The pyrimidin-2-amine unit of the sulfamethazine provided unique examples of cocrystals in which amidine and imidine forms or neutral and protonated forms of sulfamethazine are observed in 2:2 ratios. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Structures of both solvates were determined by single-crystal X-ray diffraction. It may be noted that the solvates of sulfadiazine were observed in the amine or the imine form, which have been well studied in the literature. In the present example of the two solvates of the urea-derived sulfadiazine the bond distances and bond angles among the constituent atoms of the diazine ring suggested that both solvates were in amine form. The crystal structure of H3Sulfaurea·DMF (triclinic P 1̅ space group, Z = 2) further revealed that it had hydrogen-bonded homodimeric amine–amine synthons (B in Figure ) in the self-assembly.…”
Section: Resultsmentioning
confidence: 58%
“…Structures of both solvates were determined by single-crystal X-ray diffraction. It may be noted that the solvates of sulfadiazine were observed in the amine or the imine form, which have been well studied in the literature. In the present example of the two solvates of the urea-derived sulfadiazine the bond distances and bond angles among the constituent atoms of the diazine ring suggested that both solvates were in amine form. The crystal structure of H3Sulfaurea·DMF (triclinic P 1̅ space group, Z = 2) further revealed that it had hydrogen-bonded homodimeric amine–amine synthons (B in Figure ) in the self-assembly.…”
Section: Resultsmentioning
confidence: 58%
“…Single crystal X-ray crystallographic study revealed that the unit cell of the crystal of the salt was comprised of HSTZ cation and a Hpdc anion with half a molecule of water. The cation adopted imine form, which is the conventionally observed form in cocrystals of sulfathiazole (Singh & Baruah, 2019;Wang et al, 2018). However, in related cocrystals or salts both the tautomers were also found together (Singh & Baruah, 2019).…”
Section: Resultsmentioning
confidence: 90%
“…The cation adopted imine form, which is the conventionally observed form in cocrystals of sulfathiazole (Singh & Baruah, 2019;Wang et al, 2018). However, in related cocrystals or salts both the tautomers were also found together (Singh & Baruah, 2019). One N-H bond of the protonated amine group participated in N1-HˑˑˑO7 hydrogen bond with a bridging water molecule, which further linked an oxygen atom of carboxylate anion through O7-HˑˑˑO hydrogen bond.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The first one is sulfamethazine. The amidine tautomer, imidine tautomer, anion, and cation have been observed in the structures of sulfamethazine and its crystalline complexes. The other three APIs are piroxicam, meloxicam, and enrofloxacin, all of which showed the existence of neutral and zwitterionic molecular forms, as well as cationic and anionic states in reported structures. For sulfamethazine, piroxicam, and enrofloxacin, the proton tautomeric sites are consistent with the protonation/deprotonation sites. Meloxicam shows a little difference.…”
mentioning
confidence: 78%